Analisis Pelaksanaan Pembelajaran Tematik Menggunakan Model Contextual Teaching and Learning (CTL) Kelas III Sekolah Dasar di Era Pandemi Covid-19 - Tri Wiyoko; Megawati Megawati; Ayu Wandira (Jurnal Dimensi Pendidikan dan Pembelajaran, 2021)
The success of learning can be shown by the mastery of learning objectives by students. But what about the learning process that occurred during the Covid-19 pandemic. Is it possible that the lesson planning by the teacher at the beginning of the semester can be carried out optimally. This type of research is qualitative research. The research was conducted at SD Negeri 82/II Dusun Panjang in class III. Data obtained by making observations. The researcher went to the research location by looking at the teacher's teaching activities in Theme 6. Energy and Change. Observation of learning towards initial, core, and closing activities. The results of the analysis showed that the implementation of thematic learning with the CTL model that was applied in grade III of Elementary Schools in the Era of the COVID-19 Pandemic was well prepared by the teacher. This can be seen from the learning implementation plan that has been prepared. However, at the time of its implementation there were still obstacles, so that the learning targets to be achieved were not optimal. The stages in CTL are not carried out as planned in the Learning Implementation Plan.